Thermal, kinetic of decomposition, theoretical and experimental photoluminescent studies of two Eu3+-betadiketonate containing the 5,5′-dimethyl-2,2′-bipyridine ancillary ligand: Preparation of two efficient OLEDs devices - Queiroz, Eduarda C.; Marques, Lippy F.; Carvalho, Giovanni R.; Gomes, Emmanuel M.; Franco, Douglas F. [UNESP]; Quirino, Welber G.; Rodrigues, Jocelia S.M.; Freire, Ricardo O.; Freitas-Marques, Maria B.; Araújo, Natália R.S.; Yoshida, Maria I.; Sebastião, Rita C.O.; et al. (Elsevier, 2024)
The Eu3+-betadiketonate coordination compounds are intensively studied due to their intense photoluminescence, which places them as promising materials with different applications, such as ammunition markers, biological sensors, and mainly as electroluminescent materials in Organic Light Emitting Diodes (OLEDs). This work reports the synthesis, thermal and kinetic study, crystal structures, experimental and theoretical photoluminescence analysis of two new Eu3+-betadiketonates of general formula [Eu(tta)3(5,5′-dmbpy)] 1 and [Eu(btfa)3(5,5′-dmbpy)] 2, where Htta = 4,4,4-trifluoro-1-(2-thienyl)-1,3-butanedione, Hbtfa = 4,4,4-trifluoro-1-phenyl-1,3-butanedione and 5,5′-dmbpy = 5,5′-dimethyl-2,2′-bipyridine. Photoluminescence spectroscopy data revealed that the compounds can be sensitized directly by the metal ion or through of the excitation of the excited states of the ligand system. Due to the high quantum efficiencies found for both complexes, they were used in the preparation of two OLED devices, with these devices exhibiting excellent efficiency and color purity, making them well-suited for organic electronic applications.
Keywords: Diketonate complexes; Lanthanides; OLEDs; Photophysical properties